Techno-economic assessment of small wind turbines under la Guajira-Colombia resource conditions - Jaramillo-Cardona, Juan Pablo; Perafan-Lopez, Juan Carlos; Torres-Madroñero, José Luis; Nieto-Londoño, César; Sierra-Pérez, Julián (CT&F - Ciencia, Tecnología y Futuro, 2022)
Hydroelectric plants broadly sustain Colombian electricity demand. However, wind power emerges to improve the Colombian energy matrix and capacity, satisfying the energy demand. Thus, this study evaluates the technical and economic feasibility of projects based on Small Wind Turbines (SWTs), based on the Colombian wind resource availability. Furthermore, due to the Colombian diversity of energy sources, sensitivity to climate changes and a high percentage of non-interconnected territory, the SWTs excels as an off-grid energy system alternative. For this purpose, the annual energy production and the capacity factor of 24 SWT and the wind resource in Puerto Bolívar, La Guajira, are considered. A techno-economic study that includes cash flow analysis and net present value is used to determine economic viability, considering a financing percentage sensitivity analysis. From the results, it can be concluded that an SWT based project increases its profitability by increasing the IRR value and lowering the financing percentage. Further, the best SWT models can be related to a higher capacity factor value based on the economic phase.